PENERAPAN METODE SERVICE LEARNING DALAM PEMBEKALAN ORANG TUA TK SEJAHTERA BANDUNG UNTUK MENDUKUNG KEMANDIRIAN ANAK MENUJU SEKOLAH - Widiastuti, Ratih; Deviana, Tina; Saputra, Dinar; Ghania, Aqila Irza (Jendela Akademika, 2025)
The transition from home to school is a crucial stage for early childhood, requiring independence skills, discipline, and the ability to follow instructions. Observations at Sejahtera Kindergarten in Bandung showed that the majority of children aged 3–6 still had difficulty following teacher directions and had not yet demonstrated independent behavior, largely influenced by habits at home. To address this, the community service team conducted a parenting seminar entitled "Providing Parents to Support Children's Independence: Preparing Children from Home to School." This activity used the Service Learning method with three stages: problem identification, activity preparation, and hybrid seminar implementation, involving 32 parents and 4 teachers. The material presented included morning routines that support independence, how to provide effective instructions, and strategies for training children to do activities independently. The results of the activity showed an increased understanding of parents regarding their role in shaping children's cognitive, social-emotional, and behavioral readiness. Active participant participation demonstrated that parent education-based interventions can be an effective strategy to facilitate children's transition to school. These findings emphasize the importance of consistent parental involvement at home as a key factor in children's successful adaptation to the school environment.